2010
DOI: 10.1111/j.1365-2648.2010.05517.x
|View full text |Cite
|
Sign up to set email alerts
|

Family strategies for managing childhood cancer: using complementary and alternative medicine in Jordan

Abstract: Parents used complementary and alternative medicine to support their children's medical treatment and to use all possible methods to cure their children. The reason for parents not using complementary and alternative medicine included not being aware of complementary and alternative medicine. Most of the patients have not discussed the issue of using complementary and alternative medicine with the medical staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 14 publications
3
40
1
5
Order By: Relevance
“…An explanation for this might be that the assessment of CAM use is not a routine part of health care in Jordan. Potential interactions and benefits cannot be determined without adequate information about parental CAM behavior (Al-Qudimat, Rozmus, & Farhan, 2011).…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…An explanation for this might be that the assessment of CAM use is not a routine part of health care in Jordan. Potential interactions and benefits cannot be determined without adequate information about parental CAM behavior (Al-Qudimat, Rozmus, & Farhan, 2011).…”
Section: Background and Significancementioning
confidence: 99%
“…They can also collaborate with professional CAM practitioners to develop education programs. Al-Qudimat,et al (2011) stated that it is vital to know what CAM therapies are used by particular cultural groups and to maintain open communication about CAM therapies. The use of CAM therapies should be additionally investigated in the Middle Eastern culture.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…20 In what refers to the specific malignancies, the most discussed in the literature were breast cancer 3,11,20,24,28,[38][39][40][41][42][43] and childhood cancer -lymphoma, leukemia, retinoblastoma and solid tumors. [44][45] In oncology context, the PICs are used in combination with chemotherapy and surgery and clinical cases with poor prognosis. 17,28 Looking for, thus, aiming healing, strengthening the immune system, minimizing the signs and symptoms of the disease, improving quality of life and the incentive to continue the conventional treatment.…”
mentioning
confidence: 99%
“…3,19,[22][23] It read, also, the use of such practices with the purpose to prevent recurrent cases of the disease. 40 It was found that the biological basis of therapy, with the use of herbal medicine, is the main practice used in cancer treatment, 4,16,19,28,34,[37][38]41,[44][45] then supplements and diet. [19][20]27,34,38,[41][42][44][45] It is seen from this perspective that, among the types of alternatives, that have been emphasized is the herbal medicine.…”
mentioning
confidence: 99%
See 1 more Smart Citation